DAMPAK PERKEMBANGAN PARIWISATA TERHADAP ALIH FUNGSI LAHAN PERTANIAN DAN TINGKAT KESEJAHTERAAN MASYARAKAT DI DESA TIBUBENENG - Made Kembar Sri Budhi; Ni Nyoman Anggita Maheswari (Universitas Udayana, 2025)
Agricultural land conversion can occur due to various factors. One sector that encourages land conversion is the tourism sector. This study aims to analyze the impact of tourism development on the conversion of agricultural land and the level of community welfare in Tibubeneng Village. The data source in this research is secondary data. This research uses time series data for the last 20 years, which is obtained from the Tibubeneng Village Office and the Badung Regency Tourism Office. The analysis technique used in this research is path analysis. The results of this study indicate that the number of tourist visits directly has a significant negative effect on the conversion of agricultural land in Tibubeneng Village. Number of Tourist Accommodation has a significant positive effect on Agricultural Land Use Change in Tibubeneng Village. The Number of Tourist Visits has a positive and significant effect on the Welfare Level of the Tibubeneng Village community. The Number of Tourist Accommodations has a negative and significant effect on the Welfare Level of the Tibubeneng Village Community, while Agricultural Land Use Change directly has a positive and significant effect on the welfare of the Tibubeneng Village community.